Effectiveness of Application P6 Point Acupressure to Emesis Gravidarum at Hermina Hospital Bekasi - Astuti, Puji; Intarti, Wiwit Desi; Silalahi, Friska Junita (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
In 2019 the World Health Organization (WHO) in Indonesia obtained data on pregnant women with nausea and vomiting reaching 14.8% of all pregnancies, complaints of nausea and vomiting occur in 60-80% of primigravidas and 40-60% of multigravidas . Untreated nausea and vomiting will continue to become hyperemesis gravidarum or excessive nausea and vomiting. Management depending on the severity of symptoms, treatment consists of pharmacological and non-pharmacological therapy, even now with various complementary therapies like acupressure. Purpose of the study know effectiveness of applying acupressure point P6 to emesis gravidarum at Hermina Hospital Bekasi In 2023 . Study use method Quasi Experiment with pre-test post-test design. Sample in study this totaling 25 respondents. Retrieval technique sample use total sample. Instrument study sheet check mark observation and questionnaires. Data analysts use univariate and bivariate with the Wilcoxon test. In the research Frequency of emesis gravidarum during the pretest of 25 respondents before being given acupressure P6 had an average value (mean) of 8.9. The distribution of data (Std. Deviation) obtained was 2.52 with a minimum value of 4 and a maximum value of 13. The frequency of emesis gravidarum conditions after being given acupressure P6 had an average value (mean) of 5.6 from 25 data. The distribution of data (Std.Deviation) obtained was 1.99 with a minimum value of 4 and a maximum value of 11 after the post-test. Conclusion study there is Effectiveness of Applying P6 Point Acupressure to Emesis Gravidarum at Hermina Hospital Bekasi.